(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Determination and evaluation of the aerobic capacity of football players. Using the PWC170 test, a person’s ability to perform physical work is determined by calculating the energy expended on the work performed at a heart rate of 70 beats per minute. As can be seen from the table, the maximum oxygen consumption of the players on average for the group was a good 8 and a satisfactory 7, which indicates an incomplete training of the cardiac reserve.